2021
DOI: 10.3390/jcm10163580
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Trend of Selecting Anti-Vascular Endothelial Growth Factor Agents for the Initial Treatment of Neovascular Age-Related Macular Degeneration and Polypoidal Choroidal Vasculopathy

Abstract: BACKGROUND: This study aimed to investigate the trend of selecting ranibizumab and aflibercept for the initial treatment of neovascular age-related macular degeneration (AMD) and polypoidal choroidal vasculopathy (PCV). METHODS: This was a retrospective study that included 460 patients who were diagnosed with treatment-naïve neovascular AMD and PCV and were initially treated with either ranibizumab or aflibercept. The patients were divided into two groups: the ranibizumab group (n = 96) and the aflibercept gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, a cohort study of MrOS with 4130 participants showed that patients with hip arthritis or total hip arthroplasty were 1.27 times more likely to be frail than healthy men (95% CI 1.19:1.38) [40]. A crosssectional study of 582 elderly people over 65 years old from Spain showed that frailty was associated with a variety of bone and joint diseases, including OA [41]. A recent review reported that frailty may interfere with the in ammatory environment of normal tissues, thereby hindering joint repair and ultimately leading to the development of OA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a cohort study of MrOS with 4130 participants showed that patients with hip arthritis or total hip arthroplasty were 1.27 times more likely to be frail than healthy men (95% CI 1.19:1.38) [40]. A crosssectional study of 582 elderly people over 65 years old from Spain showed that frailty was associated with a variety of bone and joint diseases, including OA [41]. A recent review reported that frailty may interfere with the in ammatory environment of normal tissues, thereby hindering joint repair and ultimately leading to the development of OA.…”
Section: Discussionmentioning
confidence: 99%
“…However, several investigators have raised concerns regarding the potential side effects of VEGF reduction, especially in elderly patients [32][33][34] . In fact, several studies have suggested some impact of this concern in clinical practice 35,36 .…”
Section: Importance Of Predicting the Difference In Post-treatment Oc...mentioning
confidence: 99%
“…Previously, photodynamic therapy (PDT) was used as the primary treatment option for this condition. However, anti-vascular endothelial growth factor (VEGF) therapy has widely replaced PDT as an effective first-line treatment for PCV [2,3].…”
Section: Introductionmentioning
confidence: 99%